What drives social returns to education? A meta-analysis - Ying Cui; Pedro S. Martins (Global Labor Organization (GLO), 2020)
Education can generate important externalities that contribute towards economic growth and convergence. In this paper, we study the drivers of such externalities by conducting the first meta-analysis of the social returns to education literature. We analyse over 1,000 estimates from 31 articles published since 1993 that cover 15 countries. Our results indicate that: 1) spillovers slow down with economic development; 2) tertiary schooling and schooling dispersion increase spillovers; 3) spillovers are smaller under fixed-effects and IV estimators but larger when measured at the firm level; and 4) there is publication bias (but not citation bias).
Keywords: I26; I28; J24; J31; C36; 330; returns to education; education externalities